2014
DOI: 10.3233/jad-132528
|View full text |Cite
|
Sign up to set email alerts
|

Visible Virchow-Robin Spaces on Magnetic Resonance Imaging of Alzheimer's Disease Patients and Normal Elderly from the Sunnybrook Dementia Study

Abstract: Compared to women, men may be more susceptible to greater volumes of VRS, particularly in the white matter. RESULTS support the hypothesis that VRS in the white matter may be more related to AD-related vascular pathology compared to VRS found in the basal ganglia. Future work using this novel VRS segmentation tool will examine its potential utility as an imaging biomarker of vascular rather than parenchymal amyloid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
176
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(198 citation statements)
references
References 31 publications
14
176
4
4
Order By: Relevance
“…4,8,9,13,[28][29][30][31] Our study sample was relatively healthy, 20 which might partly explain a smaller increase with age than expected, because PVS are presumably correlated with the degree of cerebral small-vessel disease and amyloid deposition with increasing age. 17,18 We did not find a sex difference in the distribution of PVS, even though it has been reported in earlier studies 11,13,16 ; notably, one of these studies comprised a very large population-based sample (n ϭ ϳ1800), in which men were found to have more PVS in the basal ganglia than women, 13 while another large-scale study of patients with ischemic stroke (n ϭ 1090) found that men had more PVS in the white matter than women, but there was no sex difference in the distribution of PVS in the basal ganglia. 11 The discrepancies in the findings may be partly attributable to the differences in characteristics of the study populations.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…4,8,9,13,[28][29][30][31] Our study sample was relatively healthy, 20 which might partly explain a smaller increase with age than expected, because PVS are presumably correlated with the degree of cerebral small-vessel disease and amyloid deposition with increasing age. 17,18 We did not find a sex difference in the distribution of PVS, even though it has been reported in earlier studies 11,13,16 ; notably, one of these studies comprised a very large population-based sample (n ϭ ϳ1800), in which men were found to have more PVS in the basal ganglia than women, 13 while another large-scale study of patients with ischemic stroke (n ϭ 1090) found that men had more PVS in the white matter than women, but there was no sex difference in the distribution of PVS in the basal ganglia. 11 The discrepancies in the findings may be partly attributable to the differences in characteristics of the study populations.…”
Section: Discussioncontrasting
confidence: 51%
“…First, we used diameter to measure the severity of PVS, which may be less precise than the direct measurement of PVS volume. Indeed, semiautomatic approaches for assessing PVS volume are being developed, 16 though current volumetric methods do not cover the entire brain or work as fast as visual rating approaches. 34,35 Second, our scale includes 2 parameters (number and size) of PVS in 14 regions, which is rather time-consuming (on average 6 minutes per examination).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual counting and/or manual delineation of PVS can be time-consuming, and the development of computational methods to assess them is challenging, partly due to inconsistencies within the literature regarding PVS diameter and overlap in shape, intensity, location and size with these of lacunes [11]. Recently, [12] and [13] presented computational methods to obtain quantificative measurements of PVS and validated the usefulness of their procedures in clinical research, but both approaches are semi-automatic being, therefore, prone to interobserver variations and could be time-consuming. [14] also proposed a method for quantifying PVS using high-resolution 7T MRI scanners but the use of such field strengths, although providing good spatial resolution and signal-to-noise ratio, has limited clinical use.…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathological studies have demonstrated that the frequency and severity of white matter PVS is greater in AD than controls, and this was associated with brain Aβ load, severity of CAA and Apolipoprotein E (APOE) ε4 presence (Roher et al, 2003). The association of AD and increased white matter PVS volume has also been demonstrated using neuroimaging (Ramirez et al, 2015). PVS in the centrum semiovale (CSO-PVS) are associated with CAA-related intracerebral haemorrhage (ICH) (Charidimou et al, 2013b;Charidimou et al, 2014b) and its "haemorrhagic" markers, namely lobar microbleeds (Martinez- Ramirez et al, 2013;Yakushiji et al, 2014) and cortical superficial siderosis (Charidimou et al, 2014a).…”
Section: Mri-visible Perivascular Spaces (Pvs) -Sometimes Termed Vircmentioning
confidence: 99%